Formulation and Evaluation of Nutraceutical Dosage form from Moringa oleifera, Amaranthus caudatus, and Fagopyrum esculentum (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Recent years have seen a rise in the popularity of nutraceutical foods and related items as theimportance of nutrition for health and wellness has come to light. Their potential health benefits, which extendbeyond basic nutrition, make them extremely important in the control and management of health disorders.Nutraceutical foods are extremely rich in vital components, such as micronutrients, vitamins, minerals, andantioxidants. These components not only have a high nutritional value but also support healthy immune andphysiological systems, which can help prevent disorders related to nutrition. Objectives: This study employs threepotential crops – Fagopyrum esculentum, Amaranthus caudatus, and Moringa oleifera – to generate and assessnutraceutical granules. The exceptional nutritional profiles of these crops, which contain a range of bioactivecompounds, amino acids, minerals, and vitamins, are well known. Materials and Methods: The granules weremade using the wet granulation technique using different binders (potato and maize starch), and they were thenexamined for a number of assessment characteristics. Results: The nutraceutical granules showed improvedphysicochemical and micrometric capabilities compared to their powdered versions, the findings showed. Itwas found that the granules’ in vitro disintegration profile may reach 99.62%. Conclusion: Because of theirexceptional mineral (iron) content, they are affordable and practical alternatives to the traditional formulationsthat are available for the therapy of nutritional problems such as iron deficiency anemia.